Effect of plant cultivar, Rhizobium strain and mineral nitrogen on ureide production in soybeans, common beans and leucena - Goi, Silvia Regina; Neves, Maria Cristina Prata (Pesquisa Agropecuaria Brasileira, 2014)
The effects of plant cultivars and strain of Rhizobium on ureide transport in soybean and mineral nitrogen on ureide production and transport in soybean (Glycine max (L.) Merrill), common bean (Phaseolus vulgaris L.) and leucena (Leucaena leucocephala Lam.) were studied. No significant differences were found in the percentage of ureides in xylem sap of field grown soybean cv. PI 240-663 which was inoculated with various Rhizobium strains. Significant differences were however observed between different plant cultivars. Cultivar IAC-5 had the greatest proportion of sap nitrogen as ureides. In the glasshouse, a significant decrease was found in the ureide percentage in the xylem sap of soybean and common bean supplied with nitrate-nitrogen. Applying ammonium-nitrogen 24 hours before harvesting decreased ureide production only when nitrogenase activity was significantly inhibited. Changes in ureide concentration in root and leaf extracts reflected the changes in nodulation and ureide production of nodulated soybean and common bean but not in leucaena.